Intellectual Intelligence and Learning Experience Have No Effect on the Self Directed Learning Readiness of Students on the Medical Education Study Program - Nisa, Salwa Khairun; Rachman, Lutfi; Firmansyah, Marindra (Universitas Syiah Kuala, 2024)
Self directed learning readiness has an important role in determining student academic achievement. The analysis of intellectual intelligence and learning experience as affecting factors on self directed learning readiness of medical education students on University of Islam Malang is still unknown, therefore it needs to be researched for the better educational development strategies. The University of Islam Malang's Faculty of Medicine conducted cross-sectional descriptive analytic research with 174 eligible students as a sample. The Intelligenz Struktur test was used to assess IQ. The sum of the semester credit hours was used to examine the tes and learning experiences. A questionnaire called the Self-Directed Learning Instrument was used to gauge the level of preparedness for self-directed learning. A p-value less than 0.05 was deemed significant when the data was examined. Out of 135 pupils, 77.6% were very prepared to learn independently, whereas 2 students, or 1.1%, were not at all prepared. kids with high IQ were shown to be 1.1% prepared to learn independently, but kids with low IQ were not at all prepared to do so. Of the pupils surveyed, 63 had high levels of learning experience (46.7%) and 72 had low levels of it (41.4%), indicating a high level of self-directed learning preparation. According to the spearman correlation test, there is a weak link between self-directed learning readiness and both intellectual intelligence and learning experience (r = -0.088 and r = -0.023, respectively). Results from the ordinal logistic regression test showed that IQ had no significant effect on self-directed learning readiness (p = 0.206) and that prior learning experience had no effect on self directed learning readiness (p = 0.855). Intellectual intelligence and learning experience have no effect on students self directed learning readiness.